The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1099/vir.0.83633-0
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx mori nucleopolyhedrovirus ORF56 encodes an occlusion-derived virus protein and is not essential for budded virus production

Abstract: Bombyx mori nucleopolyhedrovirus ORF56 (Bm56) is a baculovirus core gene that is highly conserved in all baculoviruses that have had their genomes sequenced to date. Its transcripts in BmNPV-infected cells could be detected from 12 h post-infection (p.i.) and the encoded protein could be detected at 16 h p.i. by using a polyclonal antibody against glutathione S-transferase-Bm56 fusion protein. Western blot analysis showed that Bm56 is a structural component of the occlusion-derived virus nucleocapsid. Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 17 publications
3
25
0
3
Order By: Relevance
“…It was previously reported that deletion of ac68 did not impact the production of OBs, whereas deletion of the BmNPV homolog bm56 resulted in defective OB morphogenesis (25,52). All of our ac68 deletion constructs produced OBs with a normal appearance, as determined by light microscopy, similar to previously reported results.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…It was previously reported that deletion of ac68 did not impact the production of OBs, whereas deletion of the BmNPV homolog bm56 resulted in defective OB morphogenesis (25,52). All of our ac68 deletion constructs produced OBs with a normal appearance, as determined by light microscopy, similar to previously reported results.…”
Section: Resultssupporting
confidence: 90%
“…All ac68 mutant viruses, ac68KO1, -2, -3, and -4, produced similar levels of BV as lef3-ac68Rep and the WT AcBac. This suggests that ac68 is not required for the normal production of BV which has been previously reported (25,52). BV titers were, however, significantly reduced, as expected for both lef3-ac68 2ϫKO and lef3KO, showing that LEF3 is critical for virus replication.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…In addition, we observed that the combination of dasatinib and CA-4 enhanced cytochrome c release from mitochondria into the cytosol in HO-8910 cells. IMS protein release can result from the mitochondrial outer membrane permeabilization (MOMP), which is thought to be regulated by proteins of the Bcl-2 family (38). The Bcl-2 protein family includes proapoptotic members, such as Bax, Bad and Bcl-Xs, and antiapoptotic members, such as Bcl-2, Bcl-XL and Mcl-1.…”
Section: Discussionmentioning
confidence: 99%